2021
DOI: 10.1098/rsif.2021.0231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sharing full versus averaged social information on social influence and estimation accuracy

Abstract: The recent developments of social networks and recommender systems have dramatically increased the amount of social information shared in human communities, challenging the human ability to process it. As a result, sharing aggregated forms of social information is becoming increasingly popular. However, it is unknown whether sharing aggregated information improves people’s judgments more than sharing the full available information. Here, we compare the performance of groups in estimation tasks when social info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…This could have resulted in an underestimation bias, especially for questions in which the true value was high (this point will be discussed in more detail in the General Discussion). However, as a similar bias has been reported in previous studies (Hertwig 31 et al, 2005;Izard & Dehaene, 2008;Jayles et al, 2017Jayles et al, , 2021aJayles et al, , 2021bKao et al, 2018;Lichtenstein et al, 1978), the current results provide additional evidence that people exhibit bias in numerical estimations even in the absence of anchoring effects.…”
Section: General Trend Of Numerical Estimationsupporting
confidence: 91%
“…This could have resulted in an underestimation bias, especially for questions in which the true value was high (this point will be discussed in more detail in the General Discussion). However, as a similar bias has been reported in previous studies (Hertwig 31 et al, 2005;Izard & Dehaene, 2008;Jayles et al, 2017Jayles et al, , 2021aJayles et al, , 2021bKao et al, 2018;Lichtenstein et al, 1978), the current results provide additional evidence that people exhibit bias in numerical estimations even in the absence of anchoring effects.…”
Section: General Trend Of Numerical Estimationsupporting
confidence: 91%
“…In the article [13], an agent-based model was built using empirical distributions of personal assessments and distributions of sensitivity to social influence, as well as the effect of distance. The model was used to generate forecasts for large groups and a number of overall estimates.…”
Section: Cyberwordmentioning
confidence: 99%
“…The analysis of works devoted to the identification of multidirectional influence in social and virtual communities [8][9][10][11][12][13][14] showed that there are no methods for assessing the influence of both "formal" and "informal" leaders, political ties on a regional society, or an individual. Also in the cited works [8][9][10][11][12][13][14] more attention is paid to the influence of collective opinion on the individual, but not vice versa.…”
Section: Cyberwordmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, considering the profound ways social media 'activities' and recommendation algorithms afect collective's cognition; we ind that understanding collective dynamics also requires both exploratory and explanatory analysis of the intertwined efects social-media 'activities', individuals' cognition and 'machines' have on each other. And that more 'crisis-focused' studies on CI behavior (similar to [9,13,25]) need to be conducted, to bring together insights from the emerging ields of łcollective behaviorž [3] and łmachine behaviorž [23]. Ultimately, it is the amalgamation of adoption of policies and guidelines from research, and investigation of emerging crisis disciplines involving humans and machines that could protect both collectives and their deliberation instruments against ongoing digital disruptions.…”
Section: Moving Forwardmentioning
confidence: 99%